Piezo/photocatalytic activity of flexible BiOCl-BiOI films immobilized on SUS304 wire mesh. (August 2021) - Zhao, Qian; Hao, Liang; Li, Fei; Liu, Tongyang; He, Yiqiang; Yang, Jun; Zhang, Yifan; Lu, Yun
Highlights: Flexible BiOCl-BiOI heterojunction films were prepared by the hydrothermal method. The formation of BiOCl-BiOI heterojunction greatly enhanced photocatalytic activity. Peizoelectric field produced by slow water flow doubled the photocatalytic activity. Abstract: The hydrothermal method was used to prepare flexible BiOCl-BiOI films on one stainless steel wire mesh. Nano-flower like BiOCl-BiOI crystals consisted of nanoplates were formed, and BiOCl was uniformly distributed. The XPS (X-ray photoelectron spectroscopy) spectra confirm the formation of BiOCl-BiOI heterojunction, which enhanced the visible light absorption of the BiOI film. The photocatalytic activity of the BiOCl-BiOI film in degrading RhB and MB was elevated by at most 8.7 and 2.4 times, respectively, comparing with the individual BiOI film. We designed and constructed a piezo/photocatalytic platform in which the prepared BiOCl-BiOI films were fixed on a rotating shaft. Compared with the static state, the photocatalytic activity of the BiOCl-BiOI film was increased by 1.4 times when the shaft was rotating. We believe that the enhancement of the photocatalytic activity should be ascribed to the piezoelectric field by introducing bending deformation, which accelerated the separation of photogenerated electrons and holes. The improvement mechanism of the photocatalytic and piezo/photocatalytic performance was proposed and discussed. The flexible BiOCl-BiOI heterojunction films show significant application potential in the pollution control of fluid fields such as rivers, oceans, waterfalls, and air.